Plexciton for surface enhanced Raman scattering and emission. (2nd December 2019) - Feng, Yanting; Gao, Man; Wang, Yu; Meng, Lingyan; Sun, Mengtao
Abstract: Plexcitons are polaritonic modes that result from coherently coupled plasmons and excitons. Far‐ and near‐field properties of Ag/semiconductor core–shell nanoparticles on silica‐coated silver substrate were theoretically studied, using finite‐difference time‐domain method. Our calculations suggested that titanium dioxide (TiO2 ) would be a better coating material, useful for the design of high‐sensitive surface enhanced Raman scattering (SERS) substrate. The calculated Raman enhancement factor could be turned to as high as 4.0 × 10 10 under the 633‐nm laser excitation. Surface plasmon‐coupled emission of SERS reveals an optimal collection angle of 5°, which shows a huge back scattering of the studied system. Our theoretical results could be used as a reference for the experimental design of semiconductor‐based SERS substrate with high efficiency. Abstract : Plexcitons are polaritonic modes that result from coherently coupled plasmons and excitons. Far‐ and near‐field properties of Ag/semiconductor core–shell nanoparticles on silica‐coated silver substrate were theoretically studied. The calculated SERS enhancement factor of Ag/TiO2 core–shell nanoparticles could reach 4.0 × 10 10 under 633‐nm laser excitation. Our theoretical results could be used as a reference for the experimental design of semiconductor‐based SERS substrate with high efficiency.